ANALISIS BIBLIOMETRIK TERKAIT PENELITIAN KREATIVITAS DAN PRODUKTIVITAS PUSTAKAWAN DALAM MENDUKUNG RISET DAN INOVASI - Tupan, Tupan (UPT Perpustakaan Universitas Bengkulu, 2024)
A bibliometric analysis of creativity and productivity of librarians in research institutions was conducted with the aim of determining the development of creativity and productivity research based on years, the development of creativity and productivity research based on keywords, the distribution of main journals in research on creativity and productivity of librarians, and cluster analysis of research networks on creativity and productivity of librarians. Data collection using keywords (TITLE-ABS-KEY (